Managing Egypt’s Poor and the Politics of Benevolence, 1800-1952 - Gregory Starrett (International Institute of Islamic Thought, 2007)
In Egypt and elsewhere in the Ottoman Empire, the social safety net represented by the extended family branched off in many directions. By Mamluk times, it encompassed the patronage of wealthy and noble families who distributed food to the poor on religious festivals and during times of hardship, and who sponsored the construction of bridges, waterworks, and public fountains. In addition, mosques sometimes housed schools, soup kitchens, and hospitals; merchants regularly fed beggars; Sufi lodges housed travelers; and waqf endowments sponsored various religious and charitable activities. Ruling dynasties, including their women, created funds that sponsored orphans’ homes, paid the dowries of poor women, and provided pensions for the widows and children of soldiers killed in battle. As Ener shows in her valuable and carefully researched book, the values of ihsan (generosity) and sadaqah (almsgiving) have been applied according to ideas about charity’s legitimate beneficiaries (e.g., clerics, the poor, orphans, and women without family support). Ener traces the fortunes of the poor, the changing constellation of institutions available for their relief, and the transformation in Egyptian understanding of those entitled to such care. By the middle of the nineteenth century, the traditional “mixed economy” of relief (p. 9), which incorporated countless donors and institutions, operated alongside a more centralized set of interests and practices intended to control poor people’s movement and activities. Such practices had not been common previously (p. 15) and appear to have been unique in the Middle East (p. 29). Authorities began to distinguish between the deserving and the undesirable poor and sought to prevent able-bodied men from encroaching on urban space as beggars or “fake” mendicants and from using publicly available forms of assistance. In nineteenth-century Cairo and Alexandria, such men and peasants “absconding” from the countryside were often arrested, sent back to their home regions, and pressed into involuntary agricultural, industrial, or military service. The growing modern state was increasingly interested in controlling crime, immigration, and the flow of disease through internationalized urban spaces ...